Potentially inappropriate medications and their effect on falls during hospital admission. (18th October 2021) - Damoiseaux-Volman, Birgit A; Raven, Kimmy; Sent, Danielle; Medlock, Stephanie; Romijn, Johannes A; Abu-Hanna, Ameen; van der Velde, Nathalie
Abstract: Objective: to investigate the effect of potentially inappropriate medications (PIMs) on inpatient falls and to identify whether PIMs as defined by STOPPFall or the designated section K for falls of STOPP v2 have a stronger association with inpatient falls when compared to the general tool STOPP v2. Methods: a retrospective observational matching study using an electronic health records dataset of patients (≥70 years) admitted to an academic hospital (2015–19), including free text to identify inpatient falls. PIMs were identified using the STOPP v2, section K of STOPP v2 and STOPPFall. We first matched admissions with PIMs to those without PIMs on confounding factors. We then applied multinomial logistic regression analysis and Cox proportional hazards analysis on the matched datasets to identify effects of PIMs on inpatient falls. Results: the dataset included 16, 678 hospital admissions, with a mean age of 77.2 years. Inpatient falls occurred during 446 (2.7%) admissions. Adjusted odds ratio (OR) (95% confidence interval (CI)) for the association between PIM exposure and falls were 7.9 (6.1–10.3) for STOPP section K, 2.2 (2.0–2.5) for STOPP and 1.4 (1.3–1.5) for STOPPFall. Adjusted hazard ratio (HR) (95% CI) for the effect on time to first fall were 2.8 (2.3–3.5) for STOPP section K, 1.5 (1.3–1.6) for STOPP and 1.3 (1.2–1.5) for STOPPFall. Conclusions: we identified an independent association of PIMs on inpatient falls for all applied (de)prescribing tools. The strongest effect was identified for STOPP section K, which is restricted to high-risk medication for falls. Our results suggest that decreasing PIM exposure during hospital stay might benefit fall prevention, but intervention studies are warranted.